Predictive factors of mortality in pediatric patients with acute renal injury associated with sepsis - Marcia C. Riyuzo; Liciana V. de A. Silveira; Célia S. Macedo; José R. Fioretto (Elsevier, 2017)
Objective: To evaluate the prognosis factors of children with sepsis and acute kidney injury. Methods: This was a retrospective study of children with sepsis and acute kidney injury that were admitted to the pediatric intensive care unit (PICU) of a tertiary hospital. A multivariate analysis was performed to compare risk factors for mortality. Results: Seventy-seven children (47 males) were retrospectively studied, median age of 4 months. Mean length of hospital stay was 7.33 ± 0.16 days, 68.9% of patients received mechanical ventilation, 25.9% had oligo-anuria, and peritoneal dialysis was performed in 42.8%. The pRIFLE criteria were: injury (5.2%) and failure (94.8%), and the staging system criteria were: stage 1 (14.3%), stage 2 (29.9%), and stage 3 (55.8%). The mortality rate was 33.7%. In the multivariate analysis, the risk factors for mortality were PICU length of stay (OR = 0.615, SE = 0.1377, 95% CI = 0.469-0.805, p = 0.0004); invasive mechanical ventilation (OR = 14.599, SE = 1.1178, 95% CI = 1.673-133.7564, p = 0.0155); need for dialysis (OR = 9.714, SE = 0.8088, 95% CI = 1.990-47.410, p = 0.0049), and hypoalbuminemia (OR = 10.484, SE = 1.1147, 95% CI = 1.179-93.200, p = 0.035). Conclusions: The risk factors for mortality in children with acute kidney injury were associated with sepsis severity. Resumo: Objetivo: Avaliar os fatores prognósticos de crianças com sepse e lesão renal aguda. Métodos: Estudo retrospectivo de crianças internadas com sepse e lesão renal aguda em unidade de terapia intensiva pediátrica de serviço terciário. Usou-se a análise multivariada na comparação dos fatores de risco para mortalidade. Resultados: Foram avaliados 77 pacientes (47 masculinos) com mediana de 4 meses de idade. A média do tempo de internação foi de 7,33 ± 0,16 dias, 68,9% necessitaram de ventilação mecânica, 25,9% eram oligoanúricos e 42,8% necessitaram de diálise. A classificação da lesão renal aguda foi pRIFLE I em 5,2% e F em 94,8% e estágio 1 (14,3%), estágio 2 (29,9%) e estágio 3 (55,8%). A taxa de mortalidade foi de 33,7%. Na análise multivariada os fatores de risco foram tempo de internação (OR = 0,615 erro padrão = 0,1377, 95% CI = 0,469-0,805, p = 0,0004), ventilação mecânica (OR = 14,599, erro padrão = 1,1178, 95% CI = 1,673-133,7564, p = 0,0155), necessidade de diálise (OR = 9,714, erro padrão = 0,8088, 95% CI = 1.990-47,410, p = 0,0049) e hipoalbuminemia (OR = 10,484, erro padrão = 1,1147, 95% CI = 1,179-93,200, p = 0,035). No modelo de Cox a sobrevida foi influenciada pela necessidade de diálise (HR = 2,952, erro padrão = 0,44862, 95% CI = 1,225-7,112, p = 0,016) e hipoalbuminemia (HR = 3,326, erro padrão = 0,59474, 95% CI = 1,037-10,670, p = 0,043). Conclusões: Os fatores de risco para mortalidade nas crianças com lesão renal aguda foram associados à gravidade da sepse. Keywords: Acute kidney injury, Sepsis, Predictive factors, Mortality, Palavras-chave: Lesão renal aguda, Sepse, Fatores preditivos, Mortalidade